IMPELEMENTASI PERMAINAN KARTU BERGAMBAR PADA PEMBELAJARAN FIQIH KELAS 2 DI SDIT ASSA'IDAH KABUPATEN BOGOR - Widiyanti, Indri; Hasanah , Tita; Fatimah , Siti (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2025)
This study aims to analyze the implementation of learning strategies through picture card games in fiqh learning at the Elementary School level. This study is qualitative, with data collection carried out through observation, interviews, and documentation, which are then described in the form of sentences that provide meaning from what is being studied. The subjects of the study were second-grade students at SDIT Assa'idah, Bogor Regency. The results of the study showed that through the picture card game learning strategy, students found it easier to understand the fiqh learning material about obligatory prayers, and were able and actively participated in prayer practices with confidence and correctly. This strategy can increase students' curiosity in learning the material